INFORMATION ON DAGESTANIS IN PAPUN ORBELIANI’S CHRONICLE “INFORMATION ON KARTLI” - Hapizov, Sahban Magomedovic; Tupcokova, Larisa Kazbekovna (History, Archeology and Ethnography of the Caucasus, 2019)
The article overviews a Georgian historical work of the 18th c. – “Information on Kartli”. This work by Papuan Orbeliani, despite its large volume, covers only a 20-year period of the Georgian history (1739-1758). The author does not provide any written sources in his chronicle. Apparently, the description of events was based on his personal memories, as well as on witness accounts. The author describes the events he himself was a part of or the information he obtained firsthand, however a vague description of events by report is mentioned throughout the text. This fact gives more credibility to this work. In 18th – first half of the 19th century his text was used in their works by other historians (Oman Kherkeulidze and Niko Dadiani).In the chronicle we focused on the information about Dagestan and its peoples, which is covered in this paper. The information mainly referred to military campaigns and raids on Georgia by Dagestan troops. At the same time, the source contains much information about political relations between Dagestan and Georgia, as well as the influence of Iran and Turkey on the situation in the region. This data allows to reconstruct some episodes of military and political history of Dagestan in the 18th c. They are also of great interest for the study of the relationship between Dagestan and Georgia in the same century. Extensive historical and philological commentaries on the translations have been provided in the paper.
Keywords: Georgia; Dagestan; Kartli; Kakheti; Heraclius II; Muhammad-nutsal